Human Resources Compensation and Employee Retention in Local Government in Uganda case of Kabale District - agaba, Moses; Bosco, Turyasingura John; Jack, Rugasira (International Journal of Management and Digital Business, 2025)
This study examined the effect of human resource compensation on employee retention in Local Governments in Uganda case of Kabale District. The objective of the study was to determine the effect of human resources compensation on employee retention in local government in Uganda case of Kabale District. A case study research design was used considering utilizing both quantitative and qualitative approaches. The study targeted 134 participants but 119 managed to respond back and these included 117 who filled the questionnaire and 02 who were interviewed. The study findings revealed that there was a positive and significant relationship between compensation and employee retention at (r = .430**, P=0.00 <0.01) and compensation and benefits positively and significantly predicted employee retention at KDLG at (Beta =.567, p=.000 <0.05). The study recommended that it’s crucial for KDLG to reevaluate their retention strategies, focusing on enhancing job satisfaction, professional development opportunities, and overall workplace conditions to mitigate turnover and ensure the retention of valuable talent. There is need for providing competitive salaries, ensuring all employees are on payroll, offering comprehensive workplace allowances and recognition programs, and equitably distributing work benefits across employees at all levels.